VEGFR1 single nucleotide polymorphisms associated with outcome in patients with metastatic renal cell carcinoma treated with sunitinib – a multicentric retrospective analysis. (January 2014) - Beuselinck, Benoit; Karadimou, Alexandra; Lambrechts, Diether; Claes, Bart; Wolter, Pascal; Couchy, Gabrielle; Berkers, Joost; van Poppel, Hendrik; Paridaens, Robert; Schöffski, Patrick; Méjean, Arnaud; Verkarre, Virginie; et al.
Abstract Background. There are no validated markers that predict outcome in metastatic renal cell cancer (mRCC) patients treated with sunitinib. Recently, single nucleotide polymorphism (SNP) rs9582036 in VEGFR1 has been proposed as a predictor of progression-free survival (PFS) and overall survival (OS) to bevacizumab in patients with pancreatic cancer and rs7993418 in VEGFR1 as predictor for PFS in mRCC-patients treated with bevacizumab. Here, we aim to study the impact of these SNPs in mRCC patients treated with sunitinib. Methods. We included patients with mRCC treated in 15 institutions in France and Belgium. Patients received sunitinib as first-line targeted therapy. We assessed response, time-to-tumor progression (TTP), OS, and clinical and biochemical parameters associated with outcome. We genotyped rs9582036 and rs7993418 as well as three other surrounding SNPs in VEGFR1: rs9554320, rs9554316 and rs9513070. Association between SNPs and treatment outcome were studied by univariate analysis and by multivariate Cox regression using relevant clinical factors associated with TTP and OS as covariates. Findings. Ninety-one patients were included. We found that mRCC patients with the CC-variant in rs9582036 in VEGFR1 have a poorer response rate (RR) (0% vs. 46%, p = 0.028), a poorer PFS (10 vs. 18 months, p = 0.033 on univariate and 0.06 on multivariate analysis) and a poorer OS (14 vs. 31 months, p = 0.019 on univariate and 0.008 on multivariate analysis) compared to patients with the AC- and AA-genotypes. mRCC patients with the AA-variant in rs9554320 in VEGFR1 have a poorer PFS (12 vs. 21 months, p = 0.0066 on univariate and 0.005 on multivariate analysis) and a poorer OS (22 vs. 34 months, p = 0.019 on univariate and 0.067 on multivariate analysis) compared to patients with the AC- and CC-genotypes. Interpretation. mRCC patients with the CC-genotype in VEGFR1 SNP rs9582036 have a poorer response rate, PFS and OS when treated with sunitinib. These findings are in agreement with the association of rs9582036 and outcome observed in bevacizumab treated pancreatic cancer patients. Prospective validation of this SNP is warranted.